The witches' advocate Basque witchcraft and the Spanish inquisition (1609-1614) - Henningsen, Gustav (Univ. of Nevada Press, 1980)
"The witches' advocate" referencia al inquisidor Alonso de Salazar.
Aus d. Dän. übers.. - Zugl.: København, Københavns Universitet, Diss., 1974
Keywords: Geschichte 1609-1614; Hekserij; Inquisitie; Inquisition - Pays basque (Espagne et France); Sorcellerie - Espagne - Pays basque espagnol; Inquisition -- Spain -- País Vasco; Witchcraft -- Spain -- País Vasco; Hexenglaube; Inquisition; Hexenprozess; Spanien; Diözese Logroño; Baskenland; Hochschulschrift; Salazar Frías, Alonso de